The Effectiveness Of Automated E-Cognitive Behavioral Therapy For Ptsd Among Sexual Abuse Victims During Childhood - Al-Wahedi, Muneera Dhaif Allah Ali (2020)
The present study aimed: First, it measures the effectiveness of automated e-CBT in reducing the symptoms of PTSD by focusing on the age of the harm, the type of sexual abuse, the type of support provided after the traumatic event, and whether the level of treatment effect varies among groups' types. Second, it examines the correlation between age difference and program effectiveness. Third, it measures the satisfaction level among PTSD patients toward the treatment they received from the proposed automated electronic cognitive behavioral therapy (e-CBT) program.